MLA 105-83 - Mineral Investigation Of The Hunter Mountain Wilderness Study Area (BLM No. CDCA-123), Inyo County, California ? Summary Statement - J. Douglas Causey (The National Institute for Occupational Safety and Health (NIOSH), 1983)
No mines are active in the Hunter Mountain Wilderness Study Area (WSA), and no mineral resources have been identified in the WSA. However, the Monarch Mine has low potential for silver, copper, tungsten, and gold resources in quartz veins; the Shirley Ann Group and Sal Group have moderate and low potential, respectively, for silver, lead, and copper resources in skarn; claims overlying the Eureka Quartzite have low potential for silica resources; and the Tourmaline N1-4 Prospect has low potential for tourmaline resources in quartz monzonite. Copper, lead, silver, tungsten, molybdenum, wollastonite and garnet occur in skarn zones between monzonitic and carbonate units. Silver, tungsten, and copper also occur in quartz veins within monzonite. Known metallic mineral deposits are small, erratic and discontinuous. The J. 0. Mine, adjacent to the northeast corner of the WSA, may contain as much as 26 million tons of subeconomic wollastonite resources. The crest of an open pit to produce that resource would extend into the WSA. No information exists on geothermal potential because no exploration has been done in the area. No occurrences of energy minerals are known within the WSA.